FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN (Media Riset Akuntansi, 2022)
The purposes of this research to analyze the effects of size, profitability, growth, leverage, and dividend policy on firm value. The company has long-term goals in order to prosper its shareholders. This goal can be achieved by increasing the value of the company which is reflected in the value of shares in the stock market. Given the importance of corporate value for the company's survival, this research is interesting to do. The population in this study were companies in the agriculture sector which were listed on the Indonesia Stock Exchange (BEI) for the period 2014-2019. The sampling technique in this study was purposive sampling. Based on this method obtained a sample size of 78. Processing and data analysis in this study using multiple linear regression. Result of research indicated that firm growth and dividend policy had no effect whereas company size and leverage influences negatively, and profitability influences positively to firm value